Does cognitive reserve reflect frailty in preoperative patients with ≥ 65 years? - Mendes, Alexandra Califórnia (2023)
Theoretical Background: In the past two decades, the elderly population undergoing surgery has increased significantly. With a substantial portion of surgical patients being over 60 years old, it is crucial to explore better ways to manage their care, as they are at higher risk of frailty and postoperative complications. Given that frailty is a strong predictor of these complications, there is a need for further research on the impact and management of frailty in surgery, including its connection to cognitive reserve. Recent studies have proposed that CR dimensions might have a protective impact not only in cognitive outcomes, but also on frailty levels. This project aims to understand the relationship between CR and the levels of frailty in the preoperative phase, since a higher frailty level is expected to predict complications during and after surgery. Methodology: The non-probability purposive sample for this study consisted of 61 participants eligible for elective surgery and cognitively healthy. Following a brief clinical interview, several instruments were administered to assess Cognitive Reserve and Frailty, which included: the Cognitive Reserve Index Questionnaire (CRIq), the Teste de Leitura de Palavras Irregulares (TeLPI), the Tilburg Frailty Indicator (TFI), and the Timed Up and Go (TUG) task. Results: CRIq raw scores exhibited negative correlations between: CRI- Work and TFITotal, CRI- Work and psychological components of the TFI, CRI- Education and psychological components of the TFI, CRI- Leisure Time and TUG and CRI- Total and TUG. Discussion: Cognitive Reserve is believed to have a protective effect against physiological and age-related changes in the brain. The ongoing discussion in this topic suggests that CR proxies might also have a protective impact on frailty levels. The results of the present study seem to suggest that: 1) having a job with higher complexity during lifespan reflects on a significant decrease in frailty in advanced ages; 2) high levels of education and high occupational attainments throughout life are correlated with the presence of less psychological components of frailty in the elderly; 3) patients that have more leisure activities are less prone to develop frailty; 4) patients with a higher CR are possibly less prone to develop frailty. The results of the present study corroborate the literature. Conclusions: The present study presents some evidence of the protective impact that CR seems to have in the frailty level in preoperative patients. Follow-up studies are necessary to investigate the degree of correlation between CR and Frailty and in which ways this relationship can be beneficial for clinical practice.